Ribosome biogenesis during cell cycle arrest fuels EMT in development and disease - Varsha Prakash (Nature Portfolio, 2019)
Ribosomal DNA transcription is essential for cell growth and division. Here, the authors show that EMT is accompanied by Snail binding to rDNA operons and Rictor association with nucleoli to fuel an induction of ribosome biogenesis during G1/S cell cycle arrest and inhibition of ribosome biogenesis hampers EMT, differentiates primary tumors and reduces metastasis.